Comparative analysis of drug registration and regulation: FDA vs. GCC approaches for ensuring safety and efficacy-a narrative review - Bhatti, Zohra; Siddique, Muhammad Irfan; M. Alotaibi, Nawaf; Laghari, Madeeha; Sundus, Ahlam (Nat. Inst. for Pharmaceutical Research and Development, 2025)
The increasing complexity of global pharmaceutical regulations presents significant challenges for drug development and market access across different jurisdictions. The Food and Drug administration (FDA) oversees all aspects related to new drug registration. The criteria for evaluating the efficacy and toxicity of a new drug are critical and require a prolonged duration of approximately 15 years. When comparing the evaluation method of FDA with the Gulf cooperation council (GCC), it is evident that the intellectual framework underlying these regulatory bodies differs significantly, making integration a challenging task. Despite this, the priority of both regulatory channels is to pledge the safety and efficacy of the candidate drug. GCC conducts all the evaluations considering the International Conference on Harmonization (ICH). Furthermore, marketing and financial strategies are keenly reviewed to improve access to effective treatments at reasonable costs and maintain foreground healthcare system. This study aims to identify and evaluate the differences and similarities in the approaches employed by FDA and GCC during registration and regulation processes of a new drug to ensure its safety and efficacy, and to provide insights into the strengths and weaknesses of each regulatory framework. This comparative analysis of FDA and GCC regulatory frameworks addresses a critical need in global pharmaceutical development. Understanding these distinct approaches to drug approval has immediate practical implications for pharmaceutical companies seeking market access across regions, while offering insights for regulatory harmonization efforts. The findings directly support improved efficiency in drug development pathways and enhanced global public health outcomes through more streamlined regulatory processes